2018
DOI: 10.3390/su10051334
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of the Flipped Classroom in the Physical Education Students’ Academic Performance in University Contexts

Abstract: This research analyzed Physical Education students' degree of academic performance with the incorporation of active methodologies, specifically flipped classroom mixed learning, restricted to evaluation periods in the months of June and September. The study focused on whether there are significant differences in this variable through the scores obtained. Through a simple random sampling, 131 students participated in this empiric-analytic research, using an ex-post-facto study with a retrospective design with q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 30 publications
3
58
0
17
Order By: Relevance
“…Student learning in PE, in general terms, has in several studies been demonstrated to be positively affected as more time is allocated to practical activities when comparing FL classes to traditionally conducted ones [69,[78][79][80][81]. In university PE, Hinojo-Lucena et al [82] have demonstrated that a FL approach improves academic performance and positively affects motivation. While some negative aspects of FL are pointed out, like the extra work-load that some students perceive [83,84], the reported challenges are far fewer than the reported advantages [84], and a recent review of FL in K-12 education concludes that FL promotes active learning, providing a neutral or positive impact on student achievement [85].…”
Section: Flipped Learningmentioning
confidence: 99%
“…Student learning in PE, in general terms, has in several studies been demonstrated to be positively affected as more time is allocated to practical activities when comparing FL classes to traditionally conducted ones [69,[78][79][80][81]. In university PE, Hinojo-Lucena et al [82] have demonstrated that a FL approach improves academic performance and positively affects motivation. While some negative aspects of FL are pointed out, like the extra work-load that some students perceive [83,84], the reported challenges are far fewer than the reported advantages [84], and a recent review of FL in K-12 education concludes that FL promotes active learning, providing a neutral or positive impact on student achievement [85].…”
Section: Flipped Learningmentioning
confidence: 99%
“…Thus, this methodological renewal incorporates new strategies that put the students at the centre of the teaching and learning process. Good examples of this are the flipped-classroom and gamification [7,8]. Hence, research that empirically analyzes the positive effects of greater motivation on the part of students with their role in class [9,10], is fundamental to lay the foundations for this new educational paradigm.…”
Section: Gamification Flipped-classroom and Motivationmentioning
confidence: 99%
“…Nevertheless, FL is suggested to have a positive influence on motivation to participate in PE among adolescents, as the attainment value and the expectation of success increase (Østerlie, 2018b), and the perceived costs of attending are reduced (Østerlie, 2018a), especially among girls. Furthermore, Hinojo-Lucena et al (2018) suggest applying FL in university PE due to its positive influence on motivation and academic performance. Compared to a more traditional approach in PE, the flipped approach allows for more time to be dedicated to practical activities and individual feedback, resulting in improved student learning in PE (Killian et al, 2016;Østerlie, 2016;Lina, 2017;Isidori et al, 2018;Sargent and Casey, 2019).…”
Section: Flipped Learning In Pementioning
confidence: 99%